2013
DOI: 10.1111/1471-0528.12414
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and health care determinants of preconceptional use of folic acid supplementation in France: results from the 2010 National Perinatal Survey

Abstract: Objectives To estimate the national prevalence and analyse the factors associated with preconceptional folic acid supplementation, including maternal sociodemographic characteristics, region of residence, birth control use and chronic diseases requiring medical care before conception.Design Cross-sectional population-based study.Setting All maternity units in France.Population A nationally representative sample of women giving birth in 2010 (n = 12,646).Methods Data came from mothers' interviews 2-3 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
3
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 34 publications
4
35
3
8
Order By: Relevance
“…Other studies have assessed folic acid supplementation before conception through the first month of pregnancy. One study in France found a prevalence of 26.5% 16 ; a population-based study in Australia found 36.0% in Victoria and 46.0% in New South Wales 17 ; a prevalence of 67.7% was reported in a study in China 18 ; and 30.0% in Spain 19 . In Brazil, a population-based study conducted with postpartum women in the southern city of Pelotas found a prevalence 32.0% of folic acid supplementation during pregnancy 20 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have assessed folic acid supplementation before conception through the first month of pregnancy. One study in France found a prevalence of 26.5% 16 ; a population-based study in Australia found 36.0% in Victoria and 46.0% in New South Wales 17 ; a prevalence of 67.7% was reported in a study in China 18 ; and 30.0% in Spain 19 . In Brazil, a population-based study conducted with postpartum women in the southern city of Pelotas found a prevalence 32.0% of folic acid supplementation during pregnancy 20 .…”
Section: Introductionmentioning
confidence: 97%
“…As for factors associated with folic acid supplementation during pregnancy, some studies have suggested that younger women, less educated, of low income, multiparous, reporting attending less than seven prenatal care visits, and having an unplanned pregnancy are less likely to use supplemental folic acid 1,[14][15][16][17][18][19][20][21] . A small number of studies have been conducted on the prevalence and factors associated with folic acid supplementation during pregnancy, especially in nationally representative samples.…”
mentioning
confidence: 99%
“…iron, folic acid certain vitamins. [2][3][4][5][6] Folic acid also prevents neural tube defects apart from erythropoiesis. 3 Since the consequences of the drug used during pregnancy may be serious and cause disability and burden to the family which may be lifelong.…”
Section: Introductionmentioning
confidence: 99%
“…Parece que a preocupação com a própria saúde, por meio da ida ao serviço de saúde e da realização de exames antes de engravidar, é comum entre essas mulheres. De fato, após o diagnóstico de uma doença que possa interferir nos resultados maternos e fetais, as mulheres que planejam engravidar e que possuem doença pré-existente são mais propensas a realizar o preparo pré-concepcional (Tort et al, 2013) de forma geral e, também, realizar preparos específicos como tratamento e controle de doenças. Neste estudo, mais da metade das mulheres com doenças pré-existentes realizou alguma medida de preparo pré-concepcional, mas essas mulheres já realizavam o controle e tratamentos das doenças pré-existentes, ou seja, não foi uma prática unicamente para engravidar, mas sim uma prática de saúde realizada pelas mulheres antes de planejarem a gravidez.…”
Section: Medidas De Preparo Pré-concepcional Realizadas Pelas Mulhereunclassified
“…No tocante à mulher que, por conta das perspectivas educacionais e profissionais, optou por engravidar mais tardiamente, a literatura reforça que tanto a maior escolaridade como uma maior renda (De Santis et al, 2013;Tort et al, 2013;Lawal, Adeleye, 2014;Stephenson et al, 2014) estão associadas com a realização do preparo pré-concepcional. Diferentemente dos resultados alcançados por estudo realizado na Inglaterra, em que há uma clara associação entre o trabalho e a realização do preparo pré-concepcional (Stepheson et al, 2014), neste estudo, a inserção da mulher no mundo do trabalho não está diretamente associada a esse tipo de ação preventiva, situação semelhante à verificada na Nigéria (Lawal, Adeleye, 2014).…”
Section: Concepciopnalunclassified